Informal care in the context of long-term health care for the elderly in Slovenia: A qualitative study - Pavlič Danica Rotar; Maksuti Alem; Panić Aleksandra; Pavleković Klara (Sciendo, 2021)
Slovenia is an aging society. Social security expenditures for the elderly are rising steadily, and the majority of Slovenians are firmly convinced that the state must provide elder care. This situation means that informal caregivers face many challenges and problems in their altruistic mission.